2001
DOI: 10.1590/s0100-879x2001000500018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of antioxidant enzyme activities in male and female rat macrophages by sex steroids

Abstract: Human and animal immune functions present sex dimorphism that seems to be mainly regulated by sex hormones. In the present study, the activities of the antioxidant enzymes total superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were measured in intraperitoneal resident macrophages from adult male and female rats. In addition to comparing males and females, we also examined the regulation of these enzyme activities in macrophages by sex steroids. GSH-Px activity did not differ betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
4
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 20 publications
6
49
4
2
Order By: Relevance
“…The higher level of cardiac CAT in females than in males reported in this study could be explained by the increased activity of SOD which catalyzes the dismutation of O 2 • -into O 2 and H 2 O 2 ; the accumulating H 2 O 2 induces the expression of CAT (Röhrdanz and Kahl 1998). Azevedo et al (2001) reported that CAT level in macrophages was significantly higher in female rats than in males, and ovariectomy led to significant reduction in its level. Massafra et al (1997), as well, found that females receiving oral contraceptives showed a significant increase in the serum CAT level, indicating that sex steroids may have an antioxidant activity mediated by CAT induction.…”
Section: Discussionsupporting
confidence: 46%
“…The higher level of cardiac CAT in females than in males reported in this study could be explained by the increased activity of SOD which catalyzes the dismutation of O 2 • -into O 2 and H 2 O 2 ; the accumulating H 2 O 2 induces the expression of CAT (Röhrdanz and Kahl 1998). Azevedo et al (2001) reported that CAT level in macrophages was significantly higher in female rats than in males, and ovariectomy led to significant reduction in its level. Massafra et al (1997), as well, found that females receiving oral contraceptives showed a significant increase in the serum CAT level, indicating that sex steroids may have an antioxidant activity mediated by CAT induction.…”
Section: Discussionsupporting
confidence: 46%
“…MnSOD protein levels are, however, only one index of superoxide metabolism; evidence suggests MnSOD activity may be regulated as well (Azevedo et al, 2001;Pedram et al, 2006;Strehlow et al, 2003). Interestingly, estrogen enhanced MnSOD activity in both female and male brains, while testosterone and DHT had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in female rats, brain mitochondrial peroxide production was lower than in mitochondria from male rats (Borras et al, 2003). Physiologic concentrations of estrogen can also protect against oxidative damage through modulation of antioxidant enzyme activity, including superoxide dismutase, catalase, and glutathione peroxidase (Azevedo et al, 2001;Murakoshi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that estradiol contributes to the physiological modulation of these enzymes in various tissues of rats and humans. It has been shown that erythrocyte GPx activity is higher in women than in men (1), and that the activities of SOD and GPx in liver (2) and SOD and CAT activities in macrophages (3) are significantly higher in female rats. The luteal content of SOD changes during the S. Peji et al ovulatory cycle in humans (4), whereas GPx activity in erythrocytes is positively correlated with plasma estradiol levels during the menstrual cycle (5).…”
Section: Introductionmentioning
confidence: 99%